Guinea : Request For A Three-Year Arrangement Under The Extended Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Guinea. (IMF Staff Country Reports; Country Report, 2017)
This paper discusses Guinea's Request for a Three-Year Arrangement Under the Extended Credit Facility (ECF). The Guinean economy has rebounded from the adverse impact of the Ebola epidemic, and growth is expected to continue to be sustained supported by buoyant mining activity and the scaling-up of infrastructure investments. The three-year ECF arrangement will help Guinea address a protracted balance of payment need and implement economic policies and reforms to foster higher and broad-based growth. The program will also play a catalytic role in mobilizing donor financing, notably from the World Bank and the European Union.